“Além de índio, ainda é doido”: o processo de internação de um indígena em uma instituição total - MUNIZ, Mariana Correa Soares (2020)
This dissertation discusses the relationship between mental health and indigenous peoples, in the context of a total institution. In 1999, indigenous mental health became a more frequent issue with the implementation of Distritos Sanitários Indígenas for the Fundação Nacional de Saúde (FUNASA). Alcoholism, use of synthetic drugs, depression and suicide are factors that, in the last decades, have contributed for indigenous people to receive more and more diagnoses of mental illness and to be referred for specialized treatment outside their territories. In this context, in 2007 the Política de Atenção Integral à Saúde Mental das Populações Indígenas (PAISMPI) was created, pointing out as a guideline to ensure the mental health of these people through appropriate measures that respect their ethnic specificity and guarantee a specific and differentiated servisse. The analysis developed here addresses two issues: understanding how policies of a general nature - particularly those aimed at mental health - can manage actions aimed at specific peoples; and to understand how the dynamics of mental health care for indigenous people are sent out of their territories. Based on the situation of an indigenous Tenetehara/Guajajara admitted to a mental institution five times between the years 2016-2019. To understand the dynamics of care, it analyzes the medical records of a Clinic located São Luís (MA). Some semi-structured interviews were also carried out with professionals who had contact with the indigenous people during their internment period. It concludes that the Clinic - as a total institution - produced destructive impacts on the life of the indigenous subject, distancing him from objects and feelings that connect him to the dimension of his self. The PAISMPI (2007) proved to be ineffective in terms of the monitoring system in indigenous mental health actions and in the permanent training of human resources.